2007
DOI: 10.3748/wjg.v13.i43.5725
|View full text |Cite
|
Sign up to set email alerts
|

CYP2E1 RsaIpolymorphism impacts on risk of colorectal cancer association with smoking and alcohol drinking

Abstract: AIM:To investigate associations between the Rsa Ⅰ polymorphism of CYP2E1 and risk of colorectal cancer. METHODS:A case-control study was conducted with 315 colorectal cancer cases (105 colon, 210 rectal) and 439 population-based controls in Jiangsu Province of China. Genomic DNA samples were assayed for restriction fragment length polymorphisms in CYP2E1 by PCR amplification followed by digestion with Rsa Ⅰ. Information on smoking and alcohol drinking was collected using a questionnaire. Odds ratios (ORs) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…13,14 In this study, we found that the protective effect of the GH1 1663A/A genotype for colorectal cancer was more notable in nonsmokers of cigarettes and nondrinkers of alcohol. The relationship between GH1 and habitual smoking and drinking is unclear, but GH1 increases production of both IGF-1 and IGFBP-3, accounting in part for the relatively high correlation between plasma IGF-1 and IGFBP-3.…”
Section: Discussionmentioning
confidence: 49%
“…13,14 In this study, we found that the protective effect of the GH1 1663A/A genotype for colorectal cancer was more notable in nonsmokers of cigarettes and nondrinkers of alcohol. The relationship between GH1 and habitual smoking and drinking is unclear, but GH1 increases production of both IGF-1 and IGFBP-3, accounting in part for the relatively high correlation between plasma IGF-1 and IGFBP-3.…”
Section: Discussionmentioning
confidence: 49%
“…2006; Gao et al, 2007;Hayashi et al, 1991;Lieber, 2004b;Ueno et al, 1996;Ueshima et al, 1996;Watanabe et al, 1994). The functional significance of this polymorphism may be due to its localization in the element response to the hepatic transcription factor HNF-1 (Hayashi et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…We set up the method previously described by Gao et al (2007) with some modifications developed in our laboratory. Briefly, PCR was performed using a final volume of 50 μl containing 150 ng of genomic DNA, 0.2 mM each dNTP, 1.5 mM MgCl 2 , 0.05 U/μl Taq polymerase (Invitrogen, USA) and 0.5 μM of each primer (5′-CCAGTCGAGTCTACAT TGTCA-3′sense and 5′-TTCATTCTGTCTTCTAACTGG-3′ anti-sense).…”
Section: Rsai/psti Polymorphism Genotypingmentioning
confidence: 99%